PERTANGGUNGJAWABAN HUKUM DOKTER: SUATU TINJAUAN DALAM PERSPEKTIR HUKUM KESEHATAN - Lira, M. Adnan (Universitas Ekasakti, 2023)
Doctors are a noble profession that must be protected from wrongful criminalization because of their duty to save human lives. This does not mean that doctors have absolute legal immunity and cannot be prosecuted if it is proven that they violated the patient's rights. The goal of this article is to examine the doctor's legal liabilities through the perpespective of medical law. Through library research, the issues are analyzed using a normative and conceptual approach to primary and secondary legal materials. As a type of contract, the relationship between doctors and patients is governed by law. As a result, a doctor can face legal consequences under both criminal and civil law. In terms of criminal law, a doctor who fails to perform his duties and profession in accordance with procedures may be subject to a number of Criminal Code provisions, particularly if the patient dies as a result of his negligence. Furthermore, any unlawful act that harms a third party gives rise to a civil law obligation on the person who unintentionally caused the injury to make up for the harm. If an intentional or negligent act results in a damage to or disability of a limb, the victim is entitled to compensation for the costs of healing as well as compensation for losses brought on by the injury or disability.